Functional gait analysis in a spinal contusion rat model. (December 2017) - Bhimani, Abhiraj D.; Kheirkhah, Pouyan; Arnone, Gregory D.; Nahhas, Cindy R.; Kumar, Prateek; Wonais, Matt; Hidrogo, Hugo; Aguilar, Eddy; Spalinski, Daniel; Gopalka, Mahie; Roth, Steven; Mehta, Ankit I.
Highlights: Analyzes different methods for comparing gait in spinal cord injury rat model. Rotating Rod test is the best test for mild spinal cord injuries. Ladder test and CatWalk test are best for moderate spinal cord injuries. BBB can be used for very severe injuries. Microsoft Kinect and VICON are very accurate but also more expensive. Abstract: Evaluating functional performance of spinal cord injury (SCI) rat models is essential for the development of novel treatments and breakthroughs. However, due to the variety of functional analysis methods available – each with its own strengths and weaknesses – it can be challenging to choose the most appropriate functional analysis test for the animal model. Therefore, we analyzed the strengths and weaknesses of five methods in order to determine which test is not only accurate and easily reproducible, but also relatively inexpensive so that it can be adopted universally. When comparing the Basso, Beattie, and Bresnahan (BBB) test, Ladder walking test, CatWalk test, Rotating Rod test, Microsoft Kinect system and VICON, we used the criteria of sensitivity, quality of data generated, statistical analysis of data, and rate of human error. These specific tests were chosen in order to compare the advantages and disadvantages of simple yet effective methods (BBB, Ladder test, and Rotating Rod test) to more complex and computerized methods (Catwalk, Microsoft Kinect and VICON).